2019
DOI: 10.1186/s13023-018-0991-3
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in the treatment of refractory chylothorax associated with lymphoproliferative disorders

Abstract: BackgroundChylothorax is a rare condition which can be associated with malignant lymphoproliferative disorders (LPDs). We retrospectively analyzed the results of the conservative treatment of 10 patients with persistent non-traumatic malignant chylothorax.ResultsConservative treatment lead to a decline of chylothorax after mean of 66 days and consisted of the treatment of the underlying disease and of simultaneous long-term supportive care (drainage of the thoracic cavity, dietary measures and nutrition manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The major etiology of non-traumatic chylothorax is malignancy of which lymphoma is one of the most common causes [11]. Indolent lymphomas like follicular and mantle cell lymphoma have been reported to cause chylothorax more often than the aggressive ones like diffuse large B-cell lymphoma [12]. Other lymphoprofilerative disorders like chronic lymphocytic leukemia have also been implicated in the etiology of chylothorax [13].…”
Section: Discussionmentioning
confidence: 99%
“…The major etiology of non-traumatic chylothorax is malignancy of which lymphoma is one of the most common causes [11]. Indolent lymphomas like follicular and mantle cell lymphoma have been reported to cause chylothorax more often than the aggressive ones like diffuse large B-cell lymphoma [12]. Other lymphoprofilerative disorders like chronic lymphocytic leukemia have also been implicated in the etiology of chylothorax [13].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the mechanism and treatment of chylous exudation are not clear. Effective chemotherapy is conducive to the spontaneous absorption of pleural effusion, which may solve the problem of chylothorax associated with hematological malignancies (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous experience has implied that auxiliary interventions, such as low-fat diet and parenteral nutrition, are important for the recovery of patients (2,5). The main factor affecting the treatment of chylothorax is whether the anti-cancer treatment aimed at the primary disease is effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review performed in a tertiary referral clinic suggested that surgery or trauma was the most common cause, with lymphoma or other malignancies accounting for only 16.7% of the cases [7]. Case reports in the literature have linked malignant causes of chylothorax to prostate carcinoma [8], gastric adenocarcinoma [9], mesothelioma [10], lymphomas [1114], small cell lung cancer [15], and chronic lymphocytic leukemia [16]. The overall prognosis for solid tumor-associated chylothorax is poor, while prognosis is good for lymphoma-associated chylothorax if remission can be achieved [17].…”
Section: Introductionmentioning
confidence: 99%